Physiological and developmental disturbances caused by Botryosphaeria dieback in the annual stems of grapevine - Moret, Florian; Jacquens, Lucile; Larignon, Philippe; Clément, Gilles; Coppin, Cindy; Noirot, Elodie; Courty, Pierre-Emmanuel; Fontaine, Florence; Adrian, Marielle; Trouvelot, Sophie (Frontiers in Plant Science, 2024)
Botryosphaeria dieback is a grapevine trunk disease caused by fungi of the Botryosphaeriaceae family, which attacks more specifically the woody tissues. The infection leads to different symptoms including a severe form with a leaf drop as well as premature plant death. Botryosphaeria dieback causes major economic losses, since no effective treatment is yet available. A better understanding is necessary to find solutions to fight this disease. In this study, our objective was to characterize the “leaf drop” form by (1) looking for the presence of pathogens in the basal internodes of stems, (2) quantifying blocked vessels by tylosis and/or gummosis, and (3) describing the impact of the disease on vine physiology (gene expression and metabolome) and development (establishment and functioning of the cambium and phellogen) at the level of xylem and phloem of basal stem internodes. Our study has shown that Botryosphaeriaceae were present in both phloem and xylem of the basal internodes of the annual stem, with xylem vessels obturated. We have also clearly demonstrated that gene expression and metabolite profiles were strongly modified in both xylem and phloem of diseased plants. Differences in stems between healthy (control, C) and diseased (D) plants were low at flowering (vines not yet symptomatic), higher at the onset of symptom expression and still present, although less marked, at full disease expression. qRT-PCR analysis showed in both phloem and xylem an overexpression of genes involved in plant defense, and a repression of genes related to meristematic activity (i.e. vascular cambium and phellogen). Metabolomic analysis showed specific fingerprints in stems of healthy and diseased plants from the onset of symptom expression, with an increase of the level of phytoalexins and mannitol, and a decrease of 1-kestose one. At the structural level, many alterations were observed in internodes, even before the onset of symptoms: a classical obstruction of xylem vessels and, for the first time, a disorganization of the secondary phloem with an obstruction of the sieve plates by callose. The disease modifies the development of both secondary phloem (liber) and phellogen. Altogether, this study combining different approaches allowed to highlight deep vine dysfunction in the internodes at the base of stems, that may explain vine decline due to Botryosphaeria dieback.